Administration of systemic antibiotics during non-surgical periodontal therapy: a consensus report - Pretzl, Bernadette; Sälzer, S.; Ehmke, B.; Schlagenhauf, U.; Dannewitz, B.; Dommisch, H.; Eickholz, Peter; Jockel-Schneider, Yvonne (Clinical oral investigations, 2019)
AimThe aim of this meta-review was to evaluate whether there is a meaningful clinical benefit regarding the use of systemic adjunctive antibiotics in the treatment of patients with periodontitis. Additionally, a consensus regarding possible recommendations for future administration of antibiotics should be reached.MethodsA structured literature search was performed by two independent investigators focusing on systematic reviews (SR) covering adjunctive systemic antibiosis during non-surgical periodontal therapy. Additionally, recent randomized clinical trials (RCT, July 2015 to July 2017) were searched systematically to update the latest SR. Results were summarized and discussed in a plenary to reach a consensus.ResultsMostly, systematic reviews and RCTs showed a significant positive effect of adjunctive systematic antibiosis compared to controls. These positive effects gain clinical relevance in patients with severe periodontal disease aged 55 years and younger.ConclusionSystemic antibiotics as an adjunct to non-surgical periodontal therapy should be sensibly administered and restrictively used. Only certain groups of periodontitis patients show a significant and clinically relevant benefit after intake of systemic antibiosis during periodontal therapy.Clinical relevanceAvoiding antibiotic resistance and possible side effects on the human microbiome should be a focus of dentists and physicians. Thus, a sensible administration of antibiotics is mandatory. This manuscript suggests guidelines for a reasonable use.
Gesehen am 11.12.2019
Published online: 29 October 2018